A LABORATORY STUDY OF FLUIDISED DRUM GRANULATION - R. Sarwono (Research Center for Chemistry - LIPI, 1995)
Performance study of laboratory scale Fluidised Drum Granulation (FDG) has been carried out using glass beads as model particles and melted wax as binder. The equipment was running well to coat the particle. The particle growth was simple, agglomerating or layering. Several process variables such as particle size, binder spray rate and amount of binder added, and drum speed were used to determine the unwanted agglomerate formation. The mass fraction of agglomerate formation increased sharply begin from initial particle size 3 mm to smaller. The transition size is 4 mm, there was virtually no agglomerate formation. Agglomerate formation also increased with' increasing binder spray rate, and varies little with drum speed and total amount of binder added.